Projection art and projection activism. (1st September 2021) - Buchanan, Andy
Abstract : This article explores the use of unauthorised projection-based artworks and messages as a form of activism, and as contextual street art. The issues of authority and permission that are central to the political nature of street art are unique in the case of projection artworks as the ephemeral and temporary nature of light-based installations skirt some of the fundamental objections to most street art and graffiti such as the damage to physical surfaces. Through the changes imposed on urban forms by light projections, the city is described as an animate entity, with various forces animating the surface at different timescales. The effect of street art is to democratise the alterations of the animate urban surface, and the effect of projection-based street art is to further democratise access to protected visual spaces, and to accelerate its animate nature.